Teacher candidate perceptions of electronic academic portfolios - Samuels, Julie E. (Kansas State University, 2006)
The purpose of this study was to determine to what extent teacher candidates perceive value in the process of constructing an electronic academic portfolio. This study will also attempt to answer what process teacher candidates used in developing their electronic academic portfolios and what value teacher candidates assign to each of the steps in the process as well as how the teacher candidate intends to use the academic portfolio during the final semester prior to the professional semester. A qualitative multi-case study was used to conduct the research. Data collected included a pre and post survey as well as three one-on-one interviews with eleven teacher candidates. Teacher candidates were also asked to keep an electronic journal to answer the following questions. 1. Describe the process you used to create your electronic academic portfolio. 2. Describe your personal frustrations with creating your electronic academic portfolio. 3. Describe your personal triumphs with creating your electronic academic portfolio. The analysis of the data took place throughout the final semester prior to the professional semester, during which time teacher candidates are taking his or her last five restricted methods courses. The researcher recruited one additional reader in the field of education. The reader was trained prior to the actual coding day by the researcher to identify themes from the pilot study. • Theme A: Pride • Theme B: Organization • Theme C: Technology Skills • Theme D: Value • Other The commonalities were coded by the reader and the researcher. The goal of this was to examine teacher candidate perceptions in creating and electronic academic portfolio. Teacher preparation programs must determine if the process of creating an electronic academic portfolio has positive effectiveness.
Keywords: Electronic academic portfolios; Teacher preperation; Education, Curriculum and Instruction (0727)